Multi-dimensional rapid appraisal technique for evaluating the sustainability of energy plantation forests in East Lombok District, Indonesia - BUDI HADI NARENDRA; WIDIATMAKA WIDIATMAKA; CECEP KUSMANA; LINA KARLINASARI; MACHFUD MACHFUD (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Narendra BH, Widiatmaka, Kusmana C, Karlinasari L, Machfud. 2019. Multi-dimensional rapid appraisal technique for evaluating the sustainability of energy plantation forests in East Lombok District, Indonesia. Biodiversitas 20: 1027-1033. The increased use of woody biomass as a renewable energy source should be supported by development of sustainable energy plantation forest. This study aims to evaluate the sustainability status of energy plantation forest in East Lombok District and to determine the leverage attributes affecting sustainability. The evaluation was carried out using rapid appraisal approach, consisting of multi-dimensional scaling (MDS) analysis to provide sustainability indices for ecological, economic and social dimensions, followed by Monte Carlo simulation to define the validity. Dominant attributes affecting the sustainability were assessed by sensitivity analysis. All analyses were executed using the R software. The evaluation of eight locations generally results in a quite sustainable status for ecological, social, and economic dimensions with the validity index values of 72.73%, 61.07%, and 58.49%, respectively. To maintain or enhance sustainability, some leverage attributes need to be prioritized for policy intervention. In the ecological dimension, increasing species diversity using some potential energy woody species should be prioritized. In the social dimension, optimizing the role and capability of forest farmer groups and their members is needed, while for the economic dimension, government should support the expanding area of energy plantation forest managed by each farmer.